Exploring the Cultural Significance of The French Colonial Legacy - Ghofrane, Bioud (Future Science, 2024)
The concept of heritage is central, encompassing both tangible and intangible aspects that define collective memory and identity. In Alge-ria, preserving colonial-era buildings has sparked debates about own-ership and terminology. Although Algeria has enacted laws to protect its cultural heritage, the application to colonial architecture remains uneven, leaving many structures vulnerable to degradation. Despite these challenges, there has been growing academic interest in Algeri-an art and architecture, fostering a nuanced understanding of their historical contexts.This article explores the cultural significance of French colonial architecture in Setif, Algeria, focusing on the nine-teenth and twentieth centuries. The study employs a mixed-methods approach, integrating docu-mentary analysis and a survey of 120 residents of Setif’s inner city. Survey results reveal diverse community perspectives: some view colonial architecture as symbols of conquest, while others see it as an integral part of Algeria's urban fabric and cultural hybridity. Many res-idents admire the architectural styles, ranging from Neoclassicism to Art Deco. In conclusion, this study contributes to ongoing discussions on heritage preservation and identity construction in post-colonial soci-eties. It highlights the need for inclusive conservation strategies that recognize diverse perspectives while protecting Algeria's architectur-al heritage as a shared cultural asset.